From Self-Transcendence to Collective Transcendence: In Search of the Order of Hierarchies in Maslow’s Transcendence - Llanos, Luis Felipe; Martínez Verduzco, Lorena (Frontiers in Psychology, 2022)
Maslow’s Human Motivation extended Theory, in its late version, proposed transcendence as one of the highest levels, inclusive or holistic in the Human consciousness. Through Meaning Theory, Victor Frankl and Paul Wong suggested that self-transcendence is a fundamental expression of our spiritual nature and a distinctive concept. However, it is not clear whether at present, with an extensive offer of individualistic currents, transcending involves a personal issue or is rather a collective issue, related to community and culture. The objective of this research is to determine if seeking personal transcendence and seeking collective transcendence are two differentiable categories, and if there is a priority among them, which would suggest an extension of the Theory. With the participation of 402 business students in Mexico, and with the help of a structured equation model, it was determined that there is a significant difference between orientation toward “I transcend” and the orientation toward “I help others transcend.” The results obtained from the selected sample indicate that individual transcendence and collective transcendence are distinguishable categories. In addition, it was found that young people prefer to seek a personal meaning rather than a collective one, which suggest that dimension of collective transcendence is prior to personal transcendence. These findings can be used to design job profiles for positions that require staff development, and it can serve as a positive pattern for life education and society.